Roland Barthes' Semiotic Analysis Of The Film Poster For Lila's Story - Dede Budianto; Mayang Pipit (International journal of technology and education research, 2026)
A film poster is a visual communication medium that serves to introduce a film and build audience expectations through the use of visual signs. This study aims to analyze the denotative, connotative, and mythical meanings in the poster for the film Cerita Lila using Roland Barthes's semiotic theory. The study employed a qualitative approach with semiotic analysis methods. The data consisted of one official poster for the film Cerita Lila, which was analyzed based on elements such as characters, color, lighting, composition, setting, typography, and visual expression. The results show that the poster not only represents the horror genre but also constructs a myth about women as figures trapped in trauma, suffering, and the supernatural world. The dominance of dark colors, the position of the main character, the presence of sleeping children, and the old house generate connotative meanings regarding psychological fear and family conflict. At the mythical level, the poster reproduces Indonesian beliefs regarding the association of old houses, long-haired women, and the supernatural world as symbols of the presence of unseen threats.